Protective effects of melatonin and omega-3 on the hippocampus and the cerebellum of adult Wistar albino rats exposed to electromagnetic fields. Issue 4 (December 2017) - Altun, Gamze; Kaplan, Suleyman; Deniz, Omur Gulsum; Kocacan, Suleyman Emre; Canan, Sinan; Davis, Devra; Marangoz, Cafer
Highlights: 900 MHz electromagnetic field (EMF) may lead to cellular damage in the central nervous system. Exposure to EMF may affect the learning and memory. Deteriorations in the structure of the neurons exposed to EMF were observed. Melatonin and omega-3 have neuroprotective effects against EMF exposure. Abstract: The purpose of the study was to investigate the effects of pulsed digital electromagnetic radiation emitted by mobile phones on the central nervous system of the adult Wistar albino rats. The study evaluated structural and functional impacts of four treatment arms: electromagnetic field (EMF) exposed; EMF exposed + melatonin treated group (EMF + Mel); EMF exposed + omega-3 (ω3) treated group (EMF + ω3); and control group (Cont). The 12-weeks-old rats were exposed to 900 MHz EMF for 60 min/day (4:00–5:00 p.m.) for 15 days. Stereological, biochemical and electrophysiological techniques were applied to evaluate protective effects of Mel and ω3. Significant cell loss in the CA1 and CA2 regions of hippocampus were observed in the EMF compared to other groups (p < 0.01). In the CA3 region of the EMF + ω3, a significant cell increase was found compared to other groups (p < 0.01). Granular cell loss was observed in the dentate gyrus of the EMF compared to the Cont (p < 0.01). EMF + ω3 has more granular cells in the cerebellum than the Cont, EMF + Mel (p < 0.01). Significant Purkinje cell loss was found in the cerebellum of EMF group compared to the other (p < 0.01). EMF + Mel and EMF + ω3 showed the same protection compared to the Cont (p > 0.05). The passive avoidance test showed that entrance latency into the dark compartment was significantly shorter in the EMF (p < 0.05). Additionally, EMF had a higher serum enzyme activity than the other groups (p < 0.01). In conclusion, our analyses confirm that EMF may lead to cellular damage in the hippocampus and the cerebellum, and that Mel and ω3 may have neuroprotective effects.